Differential glutamine metabolism in the tumor microenvironment – studies in diversity and heterogeneity: A mini-review - Claiborne, Michael D.; Leone, Robert (Frontiers in Oncology, 2022)
Increased glutamine metabolism is a hallmark of many cancer types. In recent years, our understanding of the distinct and diverse metabolic pathways through which glutamine can be utilized has grown more refined. Additionally, the different metabolic requirements of the diverse array of cell types within the tumor microenvironment complicate the strategy of targeting any particular glutamine pathway as cancer therapy. In this Mini-Review, we discuss recent advances in further clarifying the cellular fate of glutamine through different metabolic pathways. We further discuss potential promising strategies which exploit the different requirements of cells in the tumor microenvironment as it pertains to glutamine metabolism in an attempt to suppress cancer growth and enhance anti-tumor immune responses.